Use of realistic simulation in the safety of the surgical team against coronavirus: experience report (Research, Society and Development, 2021)
The purpose of this experience report is to describe the practice and results of using realistic simulation in situ, in order to simulate the flow and care of the surgical patient with suspected or confirmed contamination of SARS-CoV-2 in the transoperative period. Nurses participated in this training; nursing technicians; anesthetists; anesthesia and nursing residents; makeup artists and hygiene professionals. The high performance simulation strategy was used through the Deliberate Practice of Fast Cycles (PDCR). The memorization of each participant was repeated numerous times, in order to reduce the error and aiming to achieve mastery. At the end of the training, debriefing was carried out to extract contributions from the participants and reinforce the positive points, not valuing the error, but showing the solution. It was important to understand the feelings of anxiety and fear that the professionals involved had on the subject, and this factor collaborated and influenced the methodological strategy. It was noticed that all professionals in the front line of surgery, who were involved in the process of educational practice of realistic simulation, felt safer and more confident in coping with the emergency surgery of patients suspected of or infected with the new coronavirus.